Clinical Isolation case of Stenotrophomonas maltophilia from Libyan hospital - Aghila, Ezzeddin Sh.; Ahmed, Mohamed O; Bennour, Emad M; Samira G. Amri, Samira G. Amri (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
Stenotrophomonas maltophilia is an important nosocomial organism increasingly reported with multiple-resistance to important antimicrobial drugs. We report an isolation case of clinical Stenotrophomonas maltophilia from Libyan hospitals. Antibiotic susceptibility testing using automated system showed the multi-resistant typical phenotype of Stenotrophomonas maltophilia against Î²-lactams drugs and sensitivity for trimethoprim-sulfamethoxazole (MICs>2/38Î¼g/ml). Laboratories must understand the importance of accurate identification and recommendations for nosocomial infection which can be treated successfully with the appropriate antibiotic drugs.